Evidence of Enriched, Hadean Mantle Reservoir from 4.2-4.0 Ga zircon xenocrysts from Paleoarchean TTGs of the Singhbhum Craton, Eastern India - Trisrota Chaudhuri (Nature Portfolio, 2018)
Abstract Sensitive High-Resolution Ion Microprobe (SHRIMP) U-Pb analyses of zircons from Paleoarchean (~3.4 Ga) tonalite-gneiss called the Older Metamorphic Tonalitic Gneiss (OMTG) from the Champua area of the Singhbhum Craton, India, reveal 4.24-4.03 Ga xenocrystic zircons, suggesting that the OMTG records the hitherto unknown oldest precursor of Hadean age reported in India. Hf isotopic analyses of the Hadean xenocrysts yield unradiogenic 176Hf/177Hfinitial compositions (0.27995 ± 0.0009 to 0.28001 ± 0.0007; ɛHf[t] = −2.5 to −5.2) indicating that an enriched reservoir existed during Hadean eon in the Singhbhum cratonic mantle. Time integrated ɛHf[t] compositional array of the Hadean xenocrysts indicates a mafic protolith with 176Lu/177Hf ratio of ∼0.019 that was reworked during ∼4.2-4.0 Ga. This also suggests that separation of such an enriched reservoir from chondritic mantle took place at 4.5 ± 0.19 Ga. However, more radiogenic yet subchondritic compositions of ∼3.67 Ga (average 176Hf/177Hfinitial 0.28024 ± 0.00007) and ~3.4 Ga zircons (average 176Hf/177Hfinitial = 0.28053 ± 0.00003) from the same OMTG samples and two other Paleoarchean TTGs dated at ~3.4 Ga and ~3.3 Ga (average 176Hf/177Hfinitial is 0.28057 ± 0.00008 and 0.28060 ± 0.00003), respectively, corroborate that the enriched Hadean reservoir subsequently underwent mixing with mantle-derived juvenile magma during the Eo-Paleoarchean.